Effects of In-Ovo Glucose and Glutamine Treatment on Hatching Efficiency, Intestinal Histomorphology and Gene Expression of Digestive Enzymes in Broiler Chicks - Cöner, FI; Saçaklı, P (Journal of the Hellenic Veterinary Medical Society, 2023)
The purpose of the present study was to identify the effects of in-ovo injection of glucose and glutamine on hatching efficiency, hatching weight, liver and residual yolk weights, intestinal histomorphology and gene expressions of digestive enzymes. On the 17th day of incubation, NaCl (0.9 %), glutamine (0.5 ml 10%), glucose (0.5 ml 0.25 g/ml), and glutamine+glucose (0.25 ml 10%+0.25 ml 0.25 g/ml) were injected into the amniotic sac. In-ovo injection of glucose, glutamine and glucose+glutamine significantly decreased hatching efficiency in glucose and glutamin+glucose groups (p<0.001). This treatment did not affect hatching weight, liver and residual yolk weight in any of the groups. When the intestinal histomorphology was evaluated, in-ovo injection was found to increase the villi height/crypt depth ratio, villus width and the number of goblet cells in the jejunum; whereas villi height, crypt depth, and tunica muscularis thickness were not significantly affected by the treatments. Moreover, the ileum histomorphology in general appear not to be affected by any of the treatments as well. In-ovo glutamine injection significantly increased Suc-Iso and mTOR gene expressions (p≤0.05) compared to the control group, whereas SGLT1 gene expression was statistically indifferent. At the end of the study, while in-ovo glucose and glutamine injection had an overall negative effect on the hatching efficiency in broiler chicks.